2018
DOI: 10.1038/s41467-018-02909-6
|View full text |Cite
|
Sign up to set email alerts
|

Nanobody-triggered lockdown of VSRs reveals ligand reloading in the Golgi

Abstract: Protein degradation in lytic compartments is crucial for eukaryotic cells. At the heart of this process, vacuolar sorting receptors (VSRs) bind soluble hydrolases in the secretory pathway and release them into the vacuolar route. Sorting efficiency is suggested to result from receptor recycling. However, how and to where plant VSRs recycle remains controversial. Here we present a nanobody–epitope interaction-based protein labeling and tracking approach to dissect their anterograde and retrograde transport rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 50 publications
(64 reference statements)
3
26
0
1
Order By: Relevance
“…1B). The proposed plant model for the highly dynamic endomembrane system is well in accordance with the findings that VSRs are capable of binding their ligands already in the ER (22,23). Thus, in contrast to mammals, retromer-dependent VSR recycling in plants might occur between the TGN (6) and EMACs.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…1B). The proposed plant model for the highly dynamic endomembrane system is well in accordance with the findings that VSRs are capable of binding their ligands already in the ER (22,23). Thus, in contrast to mammals, retromer-dependent VSR recycling in plants might occur between the TGN (6) and EMACs.…”
supporting
confidence: 82%
“…Thus, in contrast to mammals, retromer-dependent VSR recycling in plants might occur between the TGN (6) and EMACs. In conflict with this, a recent study identified the Golgi as the main acceptor compartment for recycled VSRs and identified the ER only for the binding of newly synthesized receptors (23). However, the narrow interface between Golgi and ER at ER import sites (24), together with the tight ER association of the compartment, may have hampered the depiction of the precise localization based on conventional microscopic assessments.…”
mentioning
confidence: 99%
“…There is evidence that retromer vesicles are also involved in VSR recycling in plants (27), so determining the localization of the GARP complex could reveal the compartment that retrieves VSRs, an unsettled and controversial matter. The two prevailing models propose that it is either the TGN or the ER/Golgi that retrieve VSRs in plants (15,16,72). In mammalian cells, retromer vesicles are guided along microtubules to the stationary perinuclear TGN (25).…”
Section: Discussionmentioning
confidence: 99%
“…This is the traditional model for protein transport to the plant vacuole. Against this, a new emerging model for VSR-cargo proteins sorting and receptor recycling has emerged, which suggests that the VSR-cargo sorting process may be initiated already at the ER or the cis-Golgi, and then cargoes are released from the receptors in the TGN from where the VSRs are transported back through the retromer complex for another round of sorting (Niemes et al, 2010a,b;Scheuring et al, 2011;Künzl et al, 2016;Robinson and Neuhaus, 2016;Früholz et al, 2018;Salanenka et al, 2018).…”
Section: Introductionmentioning
confidence: 99%